Peran Pengembangan Pariwisata Berkelanjutan dalam Peningkatan Kesejahteraan Masyarakat Lokal - Fariz Ardhiatma (Lembaga Penelitian dan Pendidikan, 2025)
This article explores the role of sustainable tourism development in enhancing the welfare of local communities. Sustainable tourism emphasizes the long-term preservation of natural and cultural resources while providing economic benefits to the host population. The purpose of this research is to analyze how tourism strategies rooted in sustainability principles contribute to improving community income, employment opportunities, and environmental stewardship. The study applies a qualitative descriptive approach with a case study in the coastal village of Sesaot, Lombok, Indonesia. Data were collected through interviews, observations, and document analysis, and were then examined using interactive analysis techniques. The findings indicate that sustainable tourism initiatives—such as community-based tourism and eco-tourism—have significantly increased local participation, diversified income sources, and raised environmental awareness. However, challenges such as limited infrastructure and institutional support still persist. This paper concludes that sustainable tourism is a viable strategy to promote inclusive economic development, especially in rural or natural destinations. Strengthening collaboration between stakeholders and consistent policy support are essential to sustain the long-term benefits.